Routledge handbook of the environment in Southeast Asia - Hirsch, Philip 1957- (Routledge, 2017)
"The environment is one of the defining issues of our times, and it is closely linked to questions and dilemmas surrounding economic development. Southeast Asia is one of the world's most economically and demographically dynamic regions, and it is also one in which a host of environmental issues raise themselves. The Routledge Handbook of the Environment in Southeast Asia is a collection of 30 chapters dealing with the most significant scholarly debates in this rapidly growing field of study. Structured in four main parts, it gives a comprehensive regional overview of, and insight into, the environment in Southeast Asia. Wide-ranging and balanced, this Handbook promotes scholarly understanding of how environmental issues are dealt with from diverse theoretical perspectives. It offers a detailed empirical understanding of the myriad environmental problems and challenges faced in Southeast Asia. This is the first publication of its kind in this field; a helpful companion for a global audience and for scholars of Southeast Asian studies from a variety of disciplines".